As dinâmicas das ruas de Fortaleza: os processos e transformações nas vidas de pessoas às margens da cidade - Cavalcante, Clênia Trindade Lucena (2019)
In this work, I look to understand the various motivations that lead some persons to leave their homes to the point of finding in the streets a place of transitory or longstanding permanence. During the Master's research, which lasted an average of two years, in addition to the previous three years in which I worked with the same segment, as a Social Assistance Technician, it was possible to understand that some repeated motivations drive individuals away of their neighborhoods and territories. Among this issue, I can cite, without however exhausting the possibilities, the use of drug, alcohol, family quarrels, and involvement with drug trafficking. The work also aimed to understand the role and relevance attributed to public services for this population segment. I made a cutout this vast field of research, and I restrict myself to the people who are in the streets of Fortaleza and make use of the City Hall Equipment called “Centro de Referência para pessoas em situação de rua” (Pop Center). In this search for the various meanings that the homeless people attribute to municipal services, I came across as a new and unexpected event, the excessive growth of people coming to the streets as a result of compulsory expulsions from their territories by collective criminal groups known as criminal factions. This phenomenon repeatedly appeared in the speech of my interlocutors, so that I decided to open a final chapter dedicated to this theme. The interlocutors of this research walk their paths at the downtown of the Fortaleza city and make the Ferreira Square their primary home, as it is there that they shelter in the evenings for their daily rest. In order to reach the objectives proposed in this research, I was present in the City Hall's equipment talking and observing its visitors and held informal conversations with several interlocutors and interviews with users and social care professionals, as well as a bibliographic survey relevant to the theme.